2023
DOI: 10.1002/ejhf.2939
|View full text |Cite
|
Sign up to set email alerts
|

Eligibility for vericiguat in a real‐world heart failure population according to trial, guideline and label criteria: Data from the Swedish Heart Failure Registry

Abstract: AimWe investigated the eligibility for vericiguat in a real‐world heart failure (HF) population based on trial, guideline and label criteria.Methods and resultsFrom the Swedish HF registry, 23 573 patients with HF with reduced ejection fraction (HFrEF) enrolled between 2000 and 2018, with a HF duration ≥6 months, were considered. Eligibility for vericiguat was calculated based on criteria from (i) the Vericiguat Global Study in Subjects with Heart Failure and Reduced Ejection Fraction (VICTORIA) trial; (ii) Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
(108 reference statements)
0
6
0
Order By: Relevance
“…In addition, the label criteria were met more often than VICTORIA criteria. Nguyen et al [ 75 ] reported similar results upon analyzing HFrEF patients from SwedeHF, suggesting that the design of VICTORIA successfully recruited high-risk patients at the cost of limiting real-world eligibility. Nevertheless, all currently approved HF medications have been tested in both low- and high-risk patients [ 76 ].…”
Section: Real-world Experiencementioning
confidence: 84%
See 1 more Smart Citation
“…In addition, the label criteria were met more often than VICTORIA criteria. Nguyen et al [ 75 ] reported similar results upon analyzing HFrEF patients from SwedeHF, suggesting that the design of VICTORIA successfully recruited high-risk patients at the cost of limiting real-world eligibility. Nevertheless, all currently approved HF medications have been tested in both low- and high-risk patients [ 76 ].…”
Section: Real-world Experiencementioning
confidence: 84%
“…Indeed, the VICTORIA placebo group had better outcomes compared to PINNACLE patients. Two different studies have evaluated whether enrolled patients fulfilled not only VICTORIA’s inclusion criteria but also the FDA label criteria [ 74 , 75 ]. In the Korean Acute Heart Failure (KorAHF) registry [ 74 ], lower systolic blood pressure and NT-proBNP levels were the leading reasons for not fulfilling the inclusion criteria of the VICTORIA trial.…”
Section: Real-world Experiencementioning
confidence: 99%
“…Similarly, the effects of vericiguat, that recently demonstrated to improve prognosis in a high-risk HFrEF population, should be further investigated in patients with advanced HF. 41,42 Importantly, no reasons for lack of administration of GDMT were found in a large proportion of patients (ranging from 37% for ACEi/ARB/ARNI to 56% for MRA) and, similarly, no reasons for lack of titration were found in about a half of the cases. Patient-related reasons for not prescribing certain medications including frailty, cognitive impairment, dementia and lack of social and/or familial support as well as unavailability/reimbursement issues could have influenced the decision to not prescribe or uptitrate GDMT, consistently with what generally considered as clinical inertia.…”
Section: Discussionmentioning
confidence: 99%
“…HFH in the prior 6 months was the main limiting factor for eligibility. 43 EVO-HF was a multicentre prospective randomized trial comparing the proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor evolocumab (420 mg/month administered subcutaneously) plus guideline-directed medical therapy (GDMT; n = 17) versus GDMT alone (n = 22) for 1 year in patients with stable coronary artery disease and LVEF <40%, New York Heart Association class II, NT-proBNP ≥400 pg/ml, hs-TnT >10 pg/ml and low-density lipoprotein cholesterol ≥70 mg/dl. No significant changes in hs-TnT levels (primary endpoint) were observed in any group at 1 year.…”
Section: Other Medicationsmentioning
confidence: 99%
“…Only 21.4% of patients would be eligible to receive vericiguat according to VICTORIA trial selection criteria, while 47.4% of patients according to guidelines and labelling. HFH in the prior 6 months was the main limiting factor for eligibility 43 …”
Section: Medical Treatmentmentioning
confidence: 99%